ECONOMIC CRISIS, TRADE UNION AND EDUCATION (AN OVERVIEW OF INDONESIA CASE, 1999) - Soeganda Priyatna (Sosiohumaniora, 2002)
Indonesia was still enjoying the 7 % of economic growth on March 1977, when suddenly was shocked by the rapid depreciation of rupias, especially against US dollar. It was really a disaster, the price of imported goods became very high and it was a very heavy and risky burden to Indonesian economic. This also influenced the price of domestic products, due to necessity of imported parts/materials in the production process. The crisis pushed President Soeharto to step down and created the democracy euphoria. The right to organize was recognized. New trade unions were found and registered neglecting strong base membership. The decline of buying power of the people had increased the number of millions of poor children had to quit school created the education crisis. Key Word : Enonomic crisis, political crisis, trade union and education.